the Sosialisasi Penggunaan Aplikasi Quizizz Sebagai Media Pembelajaran Interaktif Pada SMA Swasta Santo Petrus Medan - Aprilianti, Charmelita; Sianturi, Jelita Fransiska; Silalahi, Anzelina; Br.Ginting, Novfiana; Sihotang, Eska Agustinus; Siahaan,M.Pd, Junita Siahaan,M.Pd (Sinesia : Jurnal Pengabdian Masyarakat, 2024)
UMKM actors in Puncak village do not understand the importance of business legality, including having a Business Identification Number (NIB). This is in line with the increasing number of UMKM actors in Puncak Village. The business licensing process, which is considered complicated and time-consuming, is the main obstacle. NIB is important for UMKM players. NIB processing is done through the OSS (Online Single Submission) system. In addition, many UMKMs in Puncak Village do not have a design or logo on their product packaging, and some existing UMKMs need to be redesigned. The method used is education on how to make NIB through OSS door to door to several UMKMs in Puncak Village. The results of this service are the issuance of NIB, packaging designs and new product logos for UMKM players in Puncak Village. This step was taken to support Puncak Village towards a smart village, where one of the main indicators is a smart economy. UMKMs play a role as the main driver of village economic activities, so strengthening UMKM players is very necessary. By having NIB and good product packaging, UMKMs in Puncak Village can contribute significantly in realizing a smarter and more competitive village economy.